ISLAMIC PROGRESS PERIOD I (650-1000 AD) - Aqsho, Muhammad; Khoir, Fahruni; Harahap, Nurhamidah; Bancin, Indriani; Arusani, Mhd Abdul Raziq; Rahma, Siti; Aulia, Vira (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2025)
The First Islamic Progress Period (650-1000 CE) was a period of Islamic progress, encompassing three periods of leadership: the Caliphate of the Rashidun Caliphate, which laid the foundation for the Islamic government system, followed by the Umayyad Caliphate, which expanded the Islamic realm. The Islamic Progress Period during the Umayyad Era was characterized by strong political stability, significant economic expansion, rapid scientific and cultural development, effective military strategy, and dynamic foreign diplomacy. All of these factors combined to help Islam become a major power in the Middle East and North Africa from the 8th to 10th centuries CE.The Caliphate of the Abbasids is known as the peak of Islamic intellectual and cultural progress. The research method used in this paper is a literature review, employing qualitative methods to obtain descriptive information from relevant sources. The First Islamic Progress Period, which lasted from 650 to 1000 CE, was a crucial period in the history of Islamic civilization. The progress of Islam during this period was evident not only in political and military aspects, but also in scientific and cultural developments. Islamic civilization succeeded in creating a rich intellectual tradition that not only influenced the Muslim world but also contributed significantly to the development of global civilization as a whole.